Regionality of Australian Apple Cider: A Sensory, Chemical and Climate Study - Madeleine L. Way; Joanna E. Jones; Rocco Longo; Robert G. Dambergs; Nigel D. Swarts (Fermentation, 2022)
Terroir is an important concept linking sensory attributes to geographically specific environmental conditions. Whilst typically applied to wine, the concept of terroir could be applied to cider. To investigate the influence of the production region on base cider total phenolic content and sensory attributes, ciders were made using ‘Fuji’ apples sourced from three major apple growing regions in Australia. Total Phenolic Content was measured using a spectrophotometry method recently validated for use in cider. A trained panel performed descriptive sensory analysis by scoring the intensity of 12 pre-determined attributes across the ciders. The intensity of sensory attributes were found to vary significantly between regions. For instance, cider made from apples grown in Stanthorpe was scored significantly higher than ciders made from apples sourced from Batlow and Huon Valley for the attribute ‘Alcoholic’. Cider made with apples from Batlow was scored significantly higher for the attribute ‘Yeasty’ compared to cider made using apples from the Huon Valley. Cider made with apples from Stanthorpe had significantly greater total phenolic content, titratable acidity, sugar content and alcohol by volume than the two other locations. These results suggest that terroir can influence apple cider, as ciders were able to be differentiated by sensory analysis based on the geographical region from where the apples were grown.